Mentoring Library School Interns at a Distance: Insights Gained from a Remote Community of Practice - Hemming, Deborah; Phinney, Jackie (Partnership, 2021)
In Fall 2020, while working remotely due to the COVID-19 pandemic, we initiated a Community of Practice (CoP) model for library school interns working on a video tutorials accessibility project for Dalhousie University Libraries. This feature outlines the background of the project, our approach to training interns remotely on Camtasia software, the development of the CoP, and our key takeaways as supervisors. While the CoP was originally intended as a source of support for the group of interns, the experience ended up being incredibly beneficial to us in our development as supervisors as we learned to mentor at a distance. We reflect on how our mentorship styles changed throughout the project and explore future directions for continuing the project with a new cohort of library interns.